PEMBELAJARAN FILSAFAT BERBASIS KEARIFAN LOKAL - Abdul Munir Mulkhan (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
One of the reasons why philosophy has been isolated from the public and daily life is that philosophical knowledge supporters tend to be unsophisticated in involving their self to the various problem of daily life discussion, even in the local, national, or global world level. It is in this isolation, the discussion topic of this paper has its meaning as a “sociology of philosophy” which supposes that the practical life is connected with the philosophical theses or just the opposite. We will analyze two problems of this topic; first, the system and model of learning the area of philosophical studies, and second, how to represent Pancasila as a part of citizen’s life which has function in conducting the stride of daily and political life in this country.